CARDIOMYOPATHIES IN CHILDREN OF THE ALTAI TERRITORY - Евгений Васильевич Скударнов; Юрий Федорович Лобанов; Ольга Ивановна Колесникова; Ольга Александровна Григоревская; Людмила Анатольевна Строзенко; Анастасия Петровна Скударнова; Наталья Александровна Журавлева; Ирина Юрьевна Болденкова (The Publishing House Medicine and Enlightenment, 2021)
The article is devoted to the actual problem of cardiology and pediatrics in general, the diagnosis of cardiomyopathies in children. 28 patients with cardiomyopathies were examined, including 14 patients with dilated cardiomyopathy, 9 patients with hypertrophic cardiomyopathy, and 5 children with undifferentiated cardiomyopathy. The article describes the main clinical symptoms and modern instrumental methods for diagnosing heart diseases, on the basis of which a pediatrician may suspect cardiomyopathy. The majority of patients with CMP had heart failure, decreased EF, and changes in the size of the myocardial thickness and heart chambers. It was found that the difficulties in diagnosing cardiomyopathies in children at the onset of the disease were due to the non-specificity of the main clinical symptoms. Diagnosis of cardiomyopathy should be based on the basis of history, clinical presentation, echocardiographic data and MRI of the myocardium.